A simple edges extraction method from complex digital images (EEMI) - Al-Ghaili A.M.; Kasim H.; Othman M.; Hassan Z. (Springer, 2023)
This paper proposes a simple Edges Extraction Method from complex digital Images (EEMI). The proposed EEMI uses a simple image processing technique to detect edges of objects and regions inside complex scenarios of images. It highlights objects edges by increasing their contrast levels and pixels intensities using special masks. EEMI mainly uses two simple masks one of which is used to detect vertical edges while the other one detects horizontal edges. Results have revealed that EEMI is a robust edge detector with inclined and complex background images. EEMI has been found simple and has simple complexity that helps reduce the computational time existent with other competitive methods. Results have confirmed that EEMIs computation time could efficiently meet real-time requirements. EEMI has been compared to other competitive operators in terms of accuracy and computation time. Springer Nature Singapore Pte Ltd. 2019.